Enriching Students’ Vocabulary Mastery Through English Spelling Bee Game - Nurwidia, Nurwidia; Baa, Sultan; Asriati, Asriati (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This study was conducted to investigate the enrichment of students' vocabulary proficiency through using the Spelling Bee game. The researcher employed a pre-experimental approach with a one-group pre-test and post-test design, collecting data through the administration of a test. The sample population for this research comprised 20 eighth-grade students, selected using the cluster random sampling technique. The finding of this research showed that the eighth grade students of SMP DDI Mattoanging have poor enough score in pre-test. After conducting the treatment of Spelling Bee Game, the students’ vocabulary mastery increase significantly. The result of the research showed that the mean score obtained the students through post-test (79.80) was higher than the pre-test (50.10). Vocabulary mastery improved 59.28% by using Spelling Bee game. Therefore, the researcher concluded that the enrichment of the students’ vocabulary mastery using Spelling Bee game was significantly enrich. Keywords— Vocabulary, Spelling Bee Game.